SWOT Analysis of Special Economic Zone - Singh Sarbjit (STIE Malangkucecwara, 2017)
For the rapid development of the economy and equal distribution of the development, Indian government has created special economic zones. These economic zones will act as a catalyst for the overall development of the region. Depending upon the resources and location each economic zone has been provided with the project. For the development of the region, it is must to know the strengths and weaknesses of the region. This study utilizes SWOT analysis to determine various internal and external factors which will impact Nagpur to be developed as the cargo hub for India. Thus provide a list of priorities for the organization and also help them to develop a strategic plan, keeping the external and internal factors in mind.